How Public Leadership Shapes Work Engagement: The Role of Work Meaningfulness and Public Service Motivation in Emergency Services - Ahmad Usman; Muhammad Zeeshan Hanif; Sheraz Ahmed (Indus Journal of Social Sciences, 2025)
This study examines how public leadership influences employee engagement by tracing two psychological links—work meaningfulness and public service motivation (PSM)—that are often mentioned in theory but less frequently tested together in practice. The inquiry builds on the Job Demands–Resources (JD–R) framework, which has been widely used to explain how employees cope with strain and sustain energy, though its application to the demanding world of emergency services has been limited. Within this framework, leadership is understood not simply as assigning roles or monitoring performance but as a resource that can orient employees, provide coherence, and signal a sense of higher mission. The argument advanced here is that when workers experience their roles as meaningful, they are more inclined to activate prosocial motives, and these motives, in turn, carry them through the physical and emotional burdens of high-stakes public work. Rescue 1122, Pakistan’s flagship emergency service, offers a particularly sharp setting for testing this reasoning: its paramedics, fire-rescue staff, and supervisors operate under constant pressure, where both stamina and commitment to public values are daily necessities. Survey data from 396 employees were analyzed using Hayes’ PROCESS Macro, and the results indicate that leadership behaviors enhance perceptions of meaningful work, which strengthens PSM and, ultimately, sustains engagement. The study contributes by showing that leadership effects unfold through layered psychological mechanisms rather than direct influence, and by grounding the evidence in a mission-intensive Global South context. Practically, the findings underscore the importance of mission framing, fairness, and recognition as central levers for sustaining frontline performance.